Albumin Description of Continuous Ambulatory Peritoneal Dialysis (CAPD) Patients in Sardjito Hospital Yogyakarta - Barkah Purwanto; Dewi Yuniasih; Metalia Puspitasari (Ahmad Dahlan Medical Journal, 2021)
Albumin profile is an important sign of nutritional status as a quality-of life parameter, whereas hypoalbuminemia has been shown to be associated with a high mortality rate for patients with End Stage Renal Disease (ESRD) undergoing dialysis including CAPD. The study was conducted to determine serum albumin levels in patients with ESRD undergoing CAPD therapy. The study was conducted in a cross-sectional manner on ESRD patients who were still actively undergoing CAPD in the outpatient Installation of Dr. Sardjito Hospital Yogyakarta until November 2018. Subjects were examined for serum albumin levels. There were 57 research subjects with the category of albumin levels <3.5 g / dL as many as 19 (33.3%), between 3.5-4.0 g / dL as many as 27 (47.3%) and albumin levels> 4.0 g / dL of 11 (19.3%). There were no significant differences in all age groups, BMI and duration of CAPD. Albumin profile can be an independent parameter of quality of life and even a predictor of mortality in CAPD patients because it does not depend on age group, BMI and length of CAPD